2010
DOI: 10.3945/jn.110.125948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fructo-Oligosaccharide on DSS-Induced Colitis Differ in Mice Fed Nonpurified and Purified Diets ,

Abstract: We investigated whether feeding a purified compared with nonpurified diet supplemented with or without fructo-oligosaccharide (FOS; 50 g/kg diet) altered the response of C57BL/6 mice to DSS-induced diarrhea. In Expt. 1, we examined disease severity in mice receiving DSS (2% in drinking water) for 5 d. In Expt. 2, we measured cecal organic acid concentrations and fecal water-holding capacity (WHC). In Expts. 3 and 4, we tested whether polycarbophil calcium (PC), a water-absorbing polymer, altered fecal WHC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…FOS supplementation by gavaging reduced DSS-induced weight loss and colonic macroscopic damage in mice fed a cereal-based fiber-rich diet (83,84). In contrast, FOS included in the purified diet (containing cellulose as the only fiber) failed to prevent mucosal damage (84,85). Clearly, TNBS and DSS models induce different courses of intestinal inflammation (79), and the effect of FOS could be model dependent.…”
Section: Fiber and Intestinal Microbiomementioning
confidence: 93%
See 2 more Smart Citations
“…FOS supplementation by gavaging reduced DSS-induced weight loss and colonic macroscopic damage in mice fed a cereal-based fiber-rich diet (83,84). In contrast, FOS included in the purified diet (containing cellulose as the only fiber) failed to prevent mucosal damage (84,85). Clearly, TNBS and DSS models induce different courses of intestinal inflammation (79), and the effect of FOS could be model dependent.…”
Section: Fiber and Intestinal Microbiomementioning
confidence: 93%
“…FOS showed a different pattern of activity when tested using the DSS model. FOS supplementation by gavaging reduced DSS-induced weight loss and colonic macroscopic damage in mice fed a cereal-based fiber-rich diet (83,84). In contrast, FOS included in the purified diet (containing cellulose as the only fiber) failed to prevent mucosal damage (84,85).…”
Section: Fiber and Intestinal Microbiomementioning
confidence: 95%
See 1 more Smart Citation
“…The protective effect of FOS was associated with an increased abundance of intestinal bifidobacteria [11], [15]. However, FOS did not attenuate inflammation in dextran sodium sulphate (DSS)-induced colitis in rats fed a purified diet [16] and supplementation of a non-purified diet with FOS reduced DSS-induced colitis in mice, whereas FOS supplementation of a purified diet exacerbated colitis [17]. Taken together, these studies suggest that the background diet affects FOS-mediated colitis reduction.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, our previous study found that in the mice fed purified diet, fructo-oligosaccharide supplementation exacerbated the symptoms of DSS-induced colitis, whereas in those fed nonpurified diet, fructo-oligosaccharide supplementation reduced the symptoms. 2) In addition, we have reported that Candida albicans, an opportunistic fungal pathogen, successfully colonized the gut of the mice fed purified diet but not those of the mice fed nonpurified diet. 3) Purified diet is widely used in nutritional studies, but purified diet is quite different from the human diet, which contains a wide variety of ingredients.…”
mentioning
confidence: 98%